2020
DOI: 10.1186/s12974-020-01871-9
|View full text |Cite
|
Sign up to set email alerts
|

A1 astrocytes contribute to murine depression-like behavior and cognitive dysfunction, which can be alleviated by IL-10 or fluorocitrate treatment

Abstract: Background Astrocytes are crucial regulators in the central nervous system. Abnormal activation of astrocytes contributes to some behavior deficits. However, mechanisms underlying the effects remain unclear. Here, we studied the activation of A1 astrocytes and their contribution to murine behavior deficits. Methods A1 astrocytes were induced by treatment with lipopolysaccharide (LPS) in vitro. The functional phenotype of astrocytes was determined by quantitative RT-PCR, ELISA, and immunohistochemistry. To ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 43 publications
3
58
1
1
Order By: Relevance
“…This result is similar to the results of other relevant studies, in which IL-10 tm1/tm1 male mice with a low expression of IL-10 exhibited defective learning and memory behaviors in the MWM test [7]. A recent study showed that IL-10 produced from microglial cells in non-learned helpless mice is necessary to maintain learning and memory [19].Intranasal administration of IL-10 increased dendritic spine density by 2.0-and 4.3-fold in the dentate gyrus of non-learned helpless and learned helpless mice [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is similar to the results of other relevant studies, in which IL-10 tm1/tm1 male mice with a low expression of IL-10 exhibited defective learning and memory behaviors in the MWM test [7]. A recent study showed that IL-10 produced from microglial cells in non-learned helpless mice is necessary to maintain learning and memory [19].Intranasal administration of IL-10 increased dendritic spine density by 2.0-and 4.3-fold in the dentate gyrus of non-learned helpless and learned helpless mice [19].…”
Section: Discussionsupporting
confidence: 92%
“…Increased IL-10 levels played a role in the process of enriched environment alleviated LPS-induced spatial learning and memory impairment [6]. IL-10 is an important molecule in the modulation of learning and memory dysfunction, as shown by the IL-10 tm1/tm1 mice that exhibited behavioral de cits in the MWM test [7].…”
Section: Introductionmentioning
confidence: 99%
“…Neurotoxic astroglial activation is also considered to contribute to neuronal damage and subsequent cognitive impairment in animal models of neurodegeneration [ 12 ]. Consistently, blocking microglia-mediated conversion of astroglia to a neurotoxic phenotype by IL-10 or fluorocitrate alleviated LPS-induced depressive-like behavior and cognitive dysfunction in mice [ 13 ]. These results suggest that neuroinflammation mediated by microglia may contribute to cognitive decline in neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies have reported that A1 astrocytes may gain neurotoxic functions and attack neurons and mature differentiated oligodendrocytes [39][40][41] . A1 reactive astrocytes can exert harmful effects because they secrete in ammatory factors such as IL-1β, IL-6, IFN-γ, and TNF-α along with the classical complement cascade genes and some unknown toxic factors deleterious to oligodendrocyte precursor cell differentiation, resulting in learning and memory impairments 13,42 . By contrast, A2 astrocyte activation was induced by ischemia, and activated A2 astrocyte are described to produce an array of neurotrophic factors, which are, therefore, considered to be protective to neurons or oligodendrocytes 16 .…”
Section: Discussionmentioning
confidence: 99%